DATAFICATION OF MEDIA WORKERS - Gonçalves, Luis; Figaro, Roseli (AoIR Selected Papers of Internet Research, 2026)
Datafication can be defined as the process of capturing, appropriating and processing user information for different capitalist purposes (Cukier and Mayer-Schoenberger, 2013; Van Dijck, 2017). In our ongoing research “Datafication of the work activity of media workers in their productive arrangements” we seek to understand the datafication of work activities. Specifically, we put a magnifying glass on the digital machinery to understand the place of value production of the media workers, as well as their specific place in the production chain of platform companies, to ascertain whether and how the work process of these professionals is datafied in its different specificities.